Perancangan Aplikasi Resep Makanan Pencegah Stunting Menggunakan Metode Design Sprint - francisca, khollydayyana mitra; Kusuma, Wahyu Teja; Khudori, Ahsanun Naseh (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Stunting is a health problem that is still a serious concern in Indonesia because of its impact on child growth. One of the main factors causing it is the lack of nutritional education for mothers and parents. To help overcome this, this study designed a food recipe application to prevent stunting using the design sprint method combined with persona, crazy 8's, and MVP (Minimum Viable Product). This combination of methods was chosen because it allows the application design process to be carried out quickly, and based on user needs. The design of this application aims to provide information about healthy food menus that are in accordance with children's nutritional needs, especially in preventing stunting. The design of the application user interface (prototype) was developed based on mobile using figma as a design tool. The application design was evaluated using the SUS method with a result of 77 which means that this application has a good level of usability with the Adjective Rating